Deciphering the Role of Host Genetics in Susceptibility to Severe COVID-19 - Carter-Timofte, Madalina Elena; Jørgensen, Sofie Eg; Freytag, Mette Ratzer; Thomsen, Michelle Mølgaard; Brinck Andersen, Nanna-Sophie; Al-Mousawi, Ali; Hait, Alon Schneider; Mogensen, Trine H. (Frontiers in Immunology, 2020)
Coronavirus disease-19 (COVID-19) describes a set of symptoms that develop following infection by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Whilst COVID-19 disease is most serious in patients with significant co-morbidities, the explanation for healthy individuals succumbing to fulminant infection is largely unexplained. In this review, we discuss the most recent findings in terms of clinical features and the host immune response, and suggest candidate immune pathways and cell types that may be defective in otherwise healthy individuals with fulminating COVID-19. On the basis of this very early knowledge we reason a potential genetic basis for increased susceptibility to SARS-CoV-2 infection. Understanding these pathways may help not only in unravelling disease pathogenesis, but also in suggesting targets for therapy and prophylaxis. Importantly such insight should instruct efforts to identify those at increased risk in order to institute preventative measures, such as prophylactic medication and/or vaccination, when such opportunities exist in the later phases of the current pandemic or during future similar pandemics.